Food‐web structures link multi‐scale processes in complex landscapes - Holly A. L. Harris; Jonathan D. Tonkin; Tara J. Murray; Richard F. Maloney; Angus R. McIntosh (Ecology, 2026)
Complex landscapes are challenging to study because both the higher level contextual and interacting lower level mechanistic processes underpinning their ecological characteristics occur simultaneously. However, food‐web structures can provide process insight in such landscapes by identifying these processes in specific contexts. Here, we used stable isotopes to identify spatially separate resources and infer resource flows underpinning food‐web structures in a braided river. We found that river resources used by mobile consumers, including birds and fish, were spatially heterogeneous. Consumer resource use was related to four key structural food‐web attributes: (1) spatiotemporal variation in foraging, (2) subsidies, (3) omnivory, and (4) ontogenetic niche shifts. Thus, both physical heterogeneity (contextual physical processes) and adaptive characteristics of consumers (mechanistic processes) were likely contributing to important food‐web structures. Identifying these food‐web structures in landscapes, across scales of resource use and spatial distribution, provides a way to identify processes and scales likely contributing to food‐web stabilization.

Rising Tide to Silent Tsunami: Unveiling the role of plastics in driving antimicrobial resistance - Emily M. Stevenson; Angus Buckling; Matthew Cole; Penelope K. Lindeque; Aimee K. Murray (Journal of Hazardous Materials, 2025)

Predictors of long-term variability in NE Atlantic plankton communities - Matthew M. Holland; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle Devlin; Eric Goberville; Pierre Hélaouët; Margarita Machairopoulou; Matthew Faith; Murray S.A. Thompson; Abigail McQuatters-Gollop (Science of The Total Environment, 2024)

Selection for antimicrobial resistance in the plastisphere - Emily M. Stevenson; Angus Buckling; Matthew Cole; Penelope K. Lindeque; Aimee K. Murray (Science of The Total Environment, 2024)

The time of emergence of climate-induced hydrologic change in Australian rivers - Andrew John; Rory Nathan; Avril Horne; Keirnan Fowler; Michael Stewardson; Murray Peel; J. Angus Webb (Journal of Hydrology, 2023)

Delayed coral recovery in a warming ocean - Kate Osborne; Angus A. Thompson; Alistair J. Cheal; Michael J. Emslie; Kerryn A. Johns; Michelle J. Jonker; Murray Logan; Ian R. Miller; Hugh P. A. Sweatman (Global Change Biology, 2017)
Climate change threatens coral reefs across the world. Intense bleaching has caused dramatic coral mortality in many tropical regions in recent decades, but less obvious chronic effects of temperature and other stressors can be equally threatening to the long‐term persistence of diverse coral‐dominated reef systems. Coral reefs persist if coral recovery rates equal or exceed average rates of mortality. While mortality from acute destructive events is often obvious and easy to measure, estimating recovery rates and investigating the factors that influence them requires long‐term commitment. Coastal development is increasing in many regions, and sea surface temperatures are also rising. The resulting chronic stresses have predictable, adverse effects on coral recovery, but the lack of consistent long‐term data sets has prevented measurement of how much coral recovery rates are actually changing. Using long‐term monitoring data from 47 reefs spread over 10 degrees of latitude on Australia's Great Barrier Reef ( GBR ), we used a modified Gompertz equation to estimate coral recovery rates following disturbance. We compared coral recovery rates in two periods: 7 years before and 7 years after an acute and widespread heat stress event on the GBR in 2002. From 2003 to 2009, there were few acute disturbances in the region, allowing us to attribute the observed shortfall in coral recovery rates to residual effects of acute heat stress plus other chronic stressors. Compared with the period before 2002, the recovery of fast‐growing Acroporidae and of “Other” slower growing hard corals slowed after 2002, doubling the time taken for modest levels of recovery. If this persists, recovery times will be increasing at a time when acute disturbances are predicted to become more frequent and intense. Our study supports the need for management actions to protect reefs from locally generated stresses, as well as urgent global action to mitigate climate change.

Environmental change in northern Belize since the latest Pleistocene - Sarah Metcalfe; Ann Breen; Malcolm Murray; Peter Furley; Anthony Fallick; Angus McKenzie (Journal of Quaternary Science, 2009)
Cores from the New River Lagoon in Belize have been analysed using a range of palaeolimnological proxies to reconstruct change since the latest Pleistocene. The combination of diatom and stable isotope analyses (supported by mineralogical and major element data) indicate that the New River Lagoon has been a freshwater system throughout the period of record. For most of this time the lagoon has been hydrologically open, but there are indications that it may have become closed in the latest Pleistocene or very early Holocene. This may have been associated with a drier climate and lower sea level. Mid‐Holocene records are consistent with those from elsewhere in the region, indicating a stable and moist climate. The late Holocene was marked by greater variability, but there is no clear evidence of any drying in the late Classic coincident with the Maya ‘collapse’ ca. AD 900. Our results indicate that the continuity of occupation at the Maya site of Lamanai on the shores of the New River Lagoon is consistent with continued access to freshwater during periods of regional climatic variability. The importance of conditions at individual sites when considering both system response and human vulnerability to climate change is emphasised. Copyright © 2009 John Wiley & Sons, Ltd.

Double primary cancers of the breast and thyroid in women: molecular analysis and genetic implications - Tuya Pal; Nancy Hamel; Danny Vesprini; Kevin Sanders; Margot Mitchell; Nada Quercia; Nathalie Ng Cheong; Angus Murray; William Foulkes; Steven A. Narod (Familial Cancer, 2001)